Forensic Medical Examination in Civil Cases: Status, Problems, Perspectives - E. Kh. Barinov; D. V. Sundukov (Общая реаниматология)
The state of forensic medical examinations in civil cases related to health harm while rendering medical services is not shown to meet the need for a legal procedure. Key words: forensic medical examination, civil procedure, medical cases.